Clinical Characteristics of Itch in Renal Transplant Recipients - Krajewski, Piotr K.; Olczyk, Piotr; Krajewska, Magdalena; Krajewski, Wojciech; Szepietowski, Jacek C. (Frontiers in Medicine, 2021)
Background: Chronic itch is the most common symptom in dermatology. End stage renal disease-associated chronic itch (ESRDCI) is a common burden affecting up to 35% of patients treated with hemodialysis. Kidney transplant (KTx) is believed to be the best renal replacement therapy leading to the elimination of ESRDCI. The study was undertaken to characterize and assess the prevalence of itch among patients after renal transplantation. Methods: Between October 2019 and January 2020 we have analyzed data of 197 patients, 121 males (61.4%) and 76 females (38.6%), aged 54.513.6 years old. The data collection was performed with specially designed questionnaire. Worst itch after renal transplantation was assessed with the use of numeral rating and visual rating scale and 4-Item Itch Questionnaire. Moreover, previous 3-days itch was evaluated. Results: The patients suffered from chronic renal disease for 20.212.3 years, mean time of the pre-transplant dialysis was 2.62.4 years and the mean time after the KTx was 8.06.5 years. The itch was present in 38.6% of the patients during the hemodialysis and in 73.7% of them ceased completely after the successful transplantation. Moreover, only in 2.63% of the cases there was no improvement. Nevertheless, the itch was reported in 42 (21.3%) renal transplant recipients (RTR) and in 22 (52.4%) of them it appeared after transplantation. The majority of patients suffering from itch were women (54.8%). Itch in the last free days was reported in 21 patients. Itch worst severity, assessed with numerical rating scale (NRS), was at 62.2 points, indicating moderate itch. In most cases (57.1%) itch affected multiple body areas. Extremities (50%) and the back (50%) were among the most frequently affected areas. The sensation had mostly short duration and was most frequently reported in the evening. Only 8 patients suffered for whole day. Hot water was the most frequently reported (16.7%) alleviating factor, whilst sweat was responsible for itch aggravation in 35.9% of cases. Conclusion: Our analysis on representative patients’ population indicates that itch after KTx is an important problem. Moreover, it is worth noticing, that more than half of the RTR did not suffer from itch during dialysis.